Role of transvaginal sonography in the diagnosis of early pregnancy failure - Khanam, Rosy; Nath, Pranoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The most crucial period of intra uterine life are the first twelve weeks of gestation, where history and clinical examination may often be inconclusive. Ultrasonography plays an important role in confirming the pregnancy, its site and viability. The objective of this study was to determine the first trimester ultrasonographic findings of a normal intrauterine pregnancy, early pregnancy failure and to have a comparative evaluation of transvaginal with transabdominal ultrasonography in the diagnosis of early pregnancy failure. Methods: Cross sectional study done in the Department of Obstetrics and Gynaecology, Silchar Medical College and Hospital from 1st June 2019 to 31st May 2020. Data were collected from 80 patients presenting to the Antenatal and Gynaecology OPD of Silchar Medical College, with positive urine beta HCG test with signs and symptoms suggestive of early pregnancy. The study was conducted during the said study period. General physical and pelvic examination done for in the cases provisional clinical diagnosis and subjected to ultrasound. Sonography by both abdominal and transvaginal method was done and findings were compared. Results: 70% of cases in this study came out to be of normal pregnancy while 30% of the total cases were of abnormal pregnancy. Various fetal developmental markers such as gestational sac, yolk sac, fetal pole, fetal heart motion, double decidual sac sign were visualised in better number of cases by transvaginal sonography than by abdominal. Amongst cases of abnormal pregnancy, parameters such as detection of abnormality in shape of gestational sac, abnormality in yolk sac were found to be better seen with transvaginal sonography than with transabdominal sonography. Measurements of mean sac diameter, crown rump length were found to be similar by both the methods. Conclusions: Combination of abdominal sonography and transvaginal sonography complements the defects of two methods and thus improves the accuracy of diagnosis. Thus it can be said that transvaginal sonography should not be used as a substitute but as a conjunct with abdominal sonography for better visualization, improved diagnosis thereby leading to better management of the patients.